Surgical technique for the treatment of renal cell carcinoma with inferior vena cava tumor thrombus: tips, tricks and oncological results - Hevia, Vital (Springerplus, 2016)
Renal cell carcinoma represents 3 % of all cancers. Around 4–10 % of cases present with inferior vena cava involvement, generally with tumor thrombus. Clinical and preoperative stage will be classified depending of the thrombus extension. A high quality preoperative workup is essential to properly plan surgical approach. Complete surgical resection of the tumor is potentially the only curative treatment, although it supposes a real challenge due to operative difficulty, potential for massive bleeding or tumor pulmonary thromboembolism. Surgery includes techniques derived from transplantation surgery and, in some cases, cardiovascular intervention with cardiopulmonary bypass. Long-term oncological outcomes after complete removal of the entire tumor burden are acceptable. In this report we describe step-by-step surgical maneuvers depending on the thrombus lever, and focusing in complete abdominal approach for the complete excision of the tumor. Moreover, a recent literature review about oncological results is reported.